Labour-Saving or Labour-Demanding? Replicating the Illumination of the 1459 Durandus - Ikeda, Mayumi (Library, 2024)
Abstract This paper examines the illumination of a group of ten surviving copies of the Rationale divinorum officiorum of Guillelmus Durandus published by Johann Fust and Peter Schöffer in 1459. It considers the methods employed for replicating the design of the illumination of this group, focusing on the opening page for Book Seven (fol. 140r), a page that uniquely demonstrates several patterns of design. Three related designs, called here Versions A, B, and C, are identified on fol. 140r. Version A is the original design, from which Versions B and C seem to have been created independently. Typically, mechanical methods for transferring designs were used to support and/or speed up the illuminator’s work, but in the Durandus they were employed so rigorously that the process must have hindered the illuminators. The impetus for the adoption of these methods, therefore, must have come from the publishers, whose goal was to produce perfect ‘illuminated facsimiles’.